Circulating miR-150 in CSF is a novel candidate biomarker for multiple sclerosis. Issue 3 (June 2016) - Bergman, Petra; Piket, Eliane; Khademi, Mohsen; James, Tojo; Brundin, Lou; Olsson, Tomas; Piehl, Fredrik; Jagodic, Maja
Abstract : Objective: To explore circulating microRNAs (miRNAs) in cell-free CSF as novel biomarkers for multiple sclerosis (MS). Methods: Profiling of miRNAs in CSF of pooled patients with clinically isolated syndrome (CIS), patients with relapsing-remitting MS, and inflammatory and noninflammatory neurologic disease controls was performed using TaqMan miRNA arrays. Two independent patient cohorts (n = 142 and n = 430) were used for validation with real-time PCR. Results: We reliably detected 88 CSF miRNAs in the exploratory cohort. Subsequent validation in 2 cohorts demonstrated significantly higher levels of miR-150 in patients with MS. Higher miR-150 levels were also observed in patients with CIS who converted to MS compared to nonconverters, and in patients initiating natalizumab treatment. Levels of miR-150 correlated with immunologic parameters including CSF cell count, immunoglobulin G index, and presence of oligoclonal bands, and with candidate protein biomarkers C-X-C motif chemokine 13, matrix metallopeptidase 9, and osteopontin. Correlation with neurofilament light chain (NFL) was observed only when NFL was adjusted for age using a method that requires further validation. Additionally, miR-150 discriminated MS from controls and CIS converters from nonconverters equally well as the most informative protein biomarkers. Following treatment with natalizumab, but not fingolimod, CSF levels of miR-150 decreased, while plasma levels increased with natalizumab and decreased with fingolimod, suggesting immune cells as a source of miR-150. Conclusions: Our findings demonstrate miR-150 as a putative novel biomarker of inflammatory active disease with the potential to be used for early diagnosis of MS. Classification of evidence: This study provides Class II evidence that CSF miR-150 distinguishes patients with MS from patients with other neurologic conditions.